MORPHOLOGICAL CHARACTERISTICS OF A NEW EXPERIMENTAL MODEL OF CHRONIC RENAL FAILURE IN THE BACKGROUND OF DIABETIC NEPHROPATHY - Shadmanov, A.K.; Okhunov, A.O.; Abdurakhmanov, F. M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Background. As is known, the modeling of chronic renal failure against the background of diabetic nephropathy is associated with the need to maximally approximate the conditions for its reproduction to the clinical one. Based on the foregoing, the priority in the reproduction of chronic renal failure should come from the modeling of diabetes mellitus, in particular diabetic nephropathy. Purpose. To develop an experimental model of chronic renal failure against the background of diabetic nephropathy. Methods. Experimental studies were carried out on rabbits with the choice of the optimal method from 5 series of experiments. The evaluation was carried out according to the abortive course of the process, the development of hyperglycemic coma, the presence of angiodillation and the reproducibility of the model. For morphological studies, tissue samples in the form of pieces of kidney tissue were taken by performing an operation under ether anesthesia. Results. The 3 stages of nephropathy identified by us during the experiment (I - minor, II - moderate and III - severe) testified to the choice of terms for modeling chronic renal failure. The main criteria for a possi- ble period of transition from nephropathy to the development of chronic renal failure is the presence of hya- linosis of microvessels with thickening of the membranes, which indicated the occurrence of irreversible angiogenic changes. This period is defined by us as 40 days of modeling diabetic nephropathy. Conclusion. In the development of chronic renal failure in a model with diabetic nephropathy, both the lack of expression of the angiogenic factor VEGF by podocytes and tubular epithelial cells and the in- creased expression of the antiangiogenic factor thrombospondin-1 in the renal glomeruli and interstitium play a certain role in the disruption of angiogenesis. Thrombospondin-1 inhibits the proliferation of endo- thelial cells stimulated by VEGF and oFRF, causing their apoptosis. As a result, the density of glomerular and peritubular capillaries decreases, glomerulosclerosis and interstitial fibrosis develop.